The Enlightenment and religion: The myths of modernity - Barnett, S. J. (2004)
The Enlightenment and religion: The myths of modernity offers a critical survey of religious change and its causes in eighteenth-century Europe, and constitutes a radical challenge to the accepted views in traditional Enlightenment studies. Focusing on Enlightenment Italy, France and England, it illustrates how the canonical view of eighteenth-century religious change has in reality been constructed upon scant evidence and assumption, in particular the idea that the thought of the enlightened led to modernity. For despite a lack of evidence, one of the fundamental assumptions of Enlightenment studies has been the assertion that there was a vibrant deist movement that formed the 'intellectual solvent' of the eighteenth century. The central claim of this book is that the immense ideological appeal of the traditional birth-of-modernity myth has meant that the actual lack of deists has been glossed over, and a quite misleading historical view has become entrenched. As a consequence more traditional forces for religious change have been given little or no attention. The book also raises hitherto neglected but fundamental methodological issues relating to the study of the eighteenth century and the ability of 'interested' contemporaries to mislead posterity. Given the current pervasive topicality of notions of modernity and postmodernity in academia, this book advances a very important discussion indeed, and will be essential reading for all students studying the period.